EVALUASI PROGRAM PENDIDIKAN BERBASIS LAPORAN AKUNTABILITAS KINERJA INSTANSI PEMERINTAH - FAISAL MADANI (Jurnal Evaluasi Pendidikan, 2011)
The research on the accountability report onthe government institutions performance (LAKIP) was intended as valuable and appropriate document for the decision makers in all government institution. The result of report was taken from the qualitative research. The study used the evaluation model of CIPO referring to Context, Input, Process, and Output. The study was conducted at the Non Formal and Informal Directorate General, Ministry of National Education and Culture, the Education Office at the West Java and Banten Province in 2011. The study found that based on context evaluation, LAKIP was assumed having very strategic and important role as the fundamental evaluation instrument which could be applied in all institutions. The study also found that there were two problems in the implementation of the LAKIP’s role. The problems were: (1) some government employees still had low knowledge on the LAKIP’s role and function, and (2) LAKIP’s format used to measure the institution performance was still incomplete. Meanwhile, based on the components of input, process, and output evaluations, LAKIP were found proper as a formal report; yet, the content of the report was not optimally used as the standard or criteria in designing and revising any policies and decisions made by the decision makers. The study suggested that the staff’s role and capacities in the Directorate of Planning and Evaluation of PAUD in the Education Office at the West Java and Banten were upgraded based on well-planned and continuing program.